No Commonality in Liquidity on Small Emerging Markets? Evidence from the Central and Eastern European Stock Exchanges - Olbryś, Joanna (Comparative Economic Research. Central and Eastern Europe, 2020)
The goal of this comparative research is to investigate intra-market commonality in liquidity on six small emerging Central and Eastern European (CEE) stock exchanges – in the Czech Republic, Hungary, Slovakia, Lithuania, Estonia, and Latvia. The CEE post-communist countries can be analyzed together as they are geographically close, and the stock markets are relatively similar. Three measures based on daily data are utilized as liquidity/illiquidity proxies: (1) a modified version of the Amihud (2002) measure, (2) the percentage relative spread, and (3) the Corwin-Schultz (2012) high-low two-day spread estimator. The OLS regression with the HAC covariance matrix estimation and the GARCH-type models are employed to explore the patterns of market-wide commonality in liquidity on the CEE stock exchanges. The main value-added comes from the methodology and the novel empirical findings. To the best of the author’s knowledge, this is the first study that investigates commonality in liquidity in the aforementioned group of countries using three liquidity proxies and the time rolling-window approach to provide robustness tests. The regressions reveal no pronounced evidence of co-movements in liquidity within the CEE markets, taken separately. What is important, the empirical results are homogeneous for all investigated markets. Therefore, no reason has been found to reject the research hypothesis that there is no commonality in liquidity on each individual market. This paper aspires to fill the gap in the knowledge of liquidity patterns on the CEE emerging markets.